The correlation between myocardial perfusion scintigraphy and three-dimensional echocardiography in ejection fraction and cardiac volumes for determination of the nearest filtering parameters - Mardanshahi, Ali Reza; Alavi, Abas; Yazdani, Jamshid; Hosseinimehr, Seyed Jalal; Khoshakhlagh, Mohammad; Dabirian, Mozhdeh; Abedi, Seyed Mahammad (World Journal of Nuclear Medicine, 2019)
End-diastolic volume (EDV), end-systolic volume (ESV), and ejection fraction (EF) are cardiac volumes that have crucial roles in diagnosis of cardiovascular diseases (CVD) in patients. There are differences between these mentioned parameters in echocardiography (Echo) and myocardial perfusion scintigraphy (MPS) in clinical practice. In this study, we determined the nearest filtering parameters in the analysis of MPS data in comparison with three-dimensional echocardiography (3DE). All of patients were in this study, and 3DE and MPS were performed for all patients at rest phase in the same day. MPS images were analyzed through quantitative gated single photon emission computer tomography (SPECT) software with Butterworth filter which was a fixed order (order = 5) and variable cutoffs (COs) of 0.3, 0.35, 0.4, 0.45, and 0.5. The EDV, ESV, and EF values were measured by 3DE and MPS and compared. Based on the above different COs, the ESVs of MPS were 15.5 ± 18 mL, 18 ± 20 mL, 21 ± 22.5 mL, 22 ± 23 mL, and 22.5 ± 23.5 mL, respectively, while ESV of 3DE was 44.4 ± 23.5 mL. It was observed as a significant difference between MPS and 3DE for ESV. The EDVs of MPS were 61.3 ± 24.5 ml, 64 ± 26.5 ml, 68 ± 29.5 ml, 72 ± 31 ml, and 76 ± 32.2 ml, respectively, while EDV of 3DE was 105 ± 30 ml, which was significantly different between two methods. The EFs of MPS were 79% ± 14%, 76% ± 13%, 73.5% ± 12%, 73.5% ± 11%, and 74% ± 11%, respectively. The EF of 3DE was 58.4% ± 10% ml. It was statistically significant difference in values of EF between SPECT analysis parameters and 3DE. It was interesting when the COs increased from 0.3 to 0.5; the cardiac volumes increased while the EF decreased. The measured ESV and EDV values were lower in females than males while the EFs of females were higher than males. Finally, we demonstrate that the nearest Cos for measuring of EF and cardiac volumes for analysis of MPS data in comparison with 3DE are 0.45 and 0.5, respectively.
Keywords: Echocardiography; ejection fraction; end-diastolic volume; end-systolic volume; myocardial perfusion scintigraphy